The Quran and the Transformation of Beliefs : (Review of Republika's Report on the Rubric of Converts) - Zulkarnaini, Zulkarnaini; Masri, Dedi (International Journal of Social Service and Research, 2024)
This study aims to explore and analyze how the Quran influenced a number of figures or scientists who later changed their beliefs or beliefs, as well as trace the background of their lives that contributed to the change in outlook on life. This phenomenon is especially observed through the study of figures who have embraced Islam after studying the Quran, as recorded in the Converts rubric in the Republika Newspaper. The research methodology uses a socio-religious phenomenon approach with a focus on the critical interpretation of hermeneutics towards the lives of converts. The selected figures will be analyzed based on their life background, religious experience before embracing Islam, and how the Quran had a significant impact on their conversion. The results showed that the Quran has a tremendous influence on human life, both psychologically, intellectually, and socio-culturally. The beauty of the language of the Qur'an, its miracles, and satisfactory answers to life's problems are the main factors that stir the hearts of converts. Some characters choose Islam because of inner conflicts, questions related to religion, conflicts in family life, or because of shock at the reality of Muslims that do not conform to initial prejudices. The benefits of this research include strengthening the arguments of the mufassir regarding the miracles of the Quran, providing stronger motivation for Muslims to explore the study of the Quran, and presenting valuable lessons for Muslims regarding the closeness of the Quran to the human heart and life. This research is expected to provide deeper insight into how the Quran can be a driver of changes in people's beliefs and outlook on life.